2001
DOI: 10.4141/a00-107
|View full text |Cite
|
Sign up to set email alerts
|

Welfare of farmed silver foxes (Vulpes vulpes) housed in sibling groups in large outdoor enclosures

Abstract: Ahola, L., Harri, M., Mononen, J., Pyykönen, T. and Kasanen, S. 2001. Welfare of farmed silver foxes (Vulpes vulpes) housed in sibling groups in large outdoor enclosures. Can. J. Anim. Sci. 81: [435][436][437][438][439][440]. The aim of the present study was to evaluate the effects of housing farmed silver foxes in large outdoor enclosures with less abundant human contacts on some behavioural and physiological welfare parameters. Farmed silver fox cubs were housed either singly in traditional fox cages or in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Many studies have investigated the influence of these early experiences in humans, including how they impact adult psychopathologies, such as depression and schizophrenia [ 4 , 5 , 6 , 7 ]. Early experiences also affect adults in many other species, including cats, [ 8 ], pigs [ 9 , 10 , 11 , 12 , 13 ], foxes [ 14 , 15 , 16 , 17 , 18 ], mice [ 19 ], and other farm animals, such as cattle and sheep [ 20 , 21 , 22 , 23 ]. For example, giving kittens additional socialisation led to owners reporting significantly higher emotional support from their cats later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the influence of these early experiences in humans, including how they impact adult psychopathologies, such as depression and schizophrenia [ 4 , 5 , 6 , 7 ]. Early experiences also affect adults in many other species, including cats, [ 8 ], pigs [ 9 , 10 , 11 , 12 , 13 ], foxes [ 14 , 15 , 16 , 17 , 18 ], mice [ 19 ], and other farm animals, such as cattle and sheep [ 20 , 21 , 22 , 23 ]. For example, giving kittens additional socialisation led to owners reporting significantly higher emotional support from their cats later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Each housing unit was video-recorded for 24 h in mid-August, at the beginning of October and at the beginning of December, as described in Ahola et al (2001). Dim red bulbs (25 W) and fluorescent lamps (38 W) covered with red plastic film were used to provide dim light for the video-recordings.…”
Section: Measured Parametersmentioning
confidence: 99%
“…Blood samples were drawn with cardiac puncture. The serum cortisol level (nmol l -1 ), as a maximum response to ACTH administration (Fraser and Broom 1990, Broom and Johnson 1993, Terlouw et al 1997, Ahola et al 2000, 2001, was analysed by a competitive immunoassay technique (Coat-A-Count Cortisol Assay by Diagnostic Products Corporation, Los Angeles, CA).…”
Section: Ahola L Et Al Effects Of Group Size and Space Allocation mentioning
confidence: 99%
“…In silver foxes themselves, it has been suggested that social housing may prove beneficial, especially during the summer, prior to the period of natural sub-adult dispersal . However, potential problems, such as aggression may occur during social housing, both in farmed fox species (Ahola et al, 2000(Ahola et al, , 2001(Ahola et al, , 2005 and many other captive social animals housed in groups (e.g. pigs; Marchant et al, 1995;calves, heifers and cows;Bøe and Faerevik, 2003).…”
Section: Introductionmentioning
confidence: 99%